Biochemical and molecular profiling of stress-responsive traits and genes in climate-resilient PGPRs - Deepanjali Gupta; Kiran P. Raverkar; Navneet Pareek; Poonam Gautam; Ajay Veer Singh; Kanchan Karki; Shivanshu Garg; Geetanjali Bhandari (Physiological and Molecular Plant Pathology, 2026)

Climate and soil properties drive microplastic enrichment patterns in agricultural soils across a multi-country survey - Martine Graf; Michaela K. Reay; Yingming Sun; Fan Ding; Siyang Ren; Kai Wang; Changrong Yan; Shitong Li; Tida Ge; Xuejun Liu; Ruimin Qi; Jixiao Cui; et al. (Environmental Pollution, 2026)

Mimosa pudica Linn. - An important medicinal plant: Pharmacognostic evaluation, bioactive compound isolation, structural elucidation, and in silico analysis - Kousik Ghosh; Karthick Gopal; Lakshmanan Narayanan; Vamsee Krishna K․; Akansha Pandey; Aswathi Mohan P․; Siva Surya; Suseem S R; S. Chitra; Preeti Sharma; Ajay Kumar Meena (Next Research, 2026)

Enhanced subsurface characterization of the Smeaheia CO2 storage reservoir field using JAYA and differential evolution based seismic inversion - G. Hema; S.P. Maurya; Ajay P. Singh; Abhay Kumar; Vivek Kumar Patel; Avinash Kumar Chouhan (International Journal of Greenhouse Gas Control, 2026)

Retraction notice to “Mechanistic interplay of dual environmental stressors: Bisphenol-A and cadmium-induced ovarian follicular damage and hepatocyte dysfunction in vivo” [Sci. Total Environ. 924 (2024) 171706] - Gokul Sudhakaran; P. Snega Priya; B. Haridevamuthu; Raghul Murugan; Jagan Kannan; Mikhlid H. Almutairi; Bader O. Almutairi; Ajay Guru; Jesu Arockiaraj (Science of The Total Environment, 2026)

Retraction notice to “Exploring bacterial communities through metagenomics during bioremediation of polycyclic aromatic hydrocarbons from contaminated sediments” [Sci. Total Environ. 842 (2022) 156794] - Haren B. Gosai; Haresh Z. Panseriya; Payal G. Patel; Ajay C. Patel; Alka Shankar; Sunita Varjani; Bharti P. Dave (Science of The Total Environment, 2026)

A hybrid chemometric and deep learning model for monitoring quality loss in thermally processed edible oils - Shruti O. Varma; Ajay L. Vishwakarma; M.R. Sonawane; Nitin P. Garad; A.C. Kumbharkhane (Food Research International, 2026)

Integrated role of mulching, sowing time, seed priming, and drip fertigation in managing leaf blight and stem rot diseases of peanut - K. S. Jadon; N. K. Jain; R. A. Jat; P. P. Thirumalaisamy; Ram Dutta; H. N. Meena; R. S. Yadav; B. C. Ajay; L. S. Rajput (Indian Phytopathology, 2026)

Quantification and characterization of soil organic carbon with different environmental gradients for the high altitude wetlands of Indian Himalaya - Narayan P. Anugraha; D. Ganguly; A. Paneer Selvam; Kakolee Banerjee; M. Harikrishna Prasad; Lakpa Tamang; Sushmita Chettri; Anupriya Soni; Rajesh Joshi; Ajay Kumar Gupta; Prakash Chhetri; Ramachandran Purvaja (Environmental Geochemistry and Health, 2026)

Harnessing aptamers for theranostic applications against multidrug-resistant bacteria: Current trends, bottlenecks and environmental relevance - N. Jaya Lakshmi; Ajay Yadav; P. Hariprasad (Journal of Environmental Chemical Engineering, 2026)

Enhanced removal of methylene blue by WO3 nanoparticles: exploring the role of surface adsorption and light-driven catalysis - Shamal D. Dhamale; Ashvini R. Morey; Ajay N. Kawade; Ramakant P. Joshi; Ravindra U. Mene (Nanotechnology for Environmental Engineering, 2026)

Hulless Barley (Hordeum vulgare L.) Variety DWRB 223 - Jogendra Singh; Omvir Singh; R. P. S. Verma; Chuni Lal; Lokendra Kumar; S. K. Bishnoi; Rekha Malik; Dinesh Kumar; OP Gupta; Charan Singh; Poonam Jasrotia; Ravindra Kumar; et al. (Indian Journal of Genetics and Plant Breeding, 2026)

The effect of microbes on adult attraction and oviposition in the small hive beetle - Yin Xun Tan; Théotime Colin; Andrew P. Allen; Md Jamil Hossain Biswas; Ajay Narendra; Fleur Ponton (Symbiosis, 2026)

Optimization of seismic inversion for acoustic impedance estimation using a hybrid simulated annealing approach: A case study from F3-block, the Netherlands - Harsha Raghuvanshi; Raghav Singh; S P Maurya; Ravi Kant; Ajay P Singh (Journal of Earth System Science, 2026)

Enhancing the therapeutic efficacy of curcumin in topical applications through nanoformulations - Rajesh Sreedharan Nair; Nashiru Billa; Ajay Babu Pazhayattil; Sarath Chandran C.; Mohammed Tahir Ansari; Kai Bin Liew; Andrew P. Morris (Natural Product Research, 2026)

Lynch syndrome integrative epidemiology and genetics (LINEAGE): rationale for cohort design - Swati G. Patel; Holli A. Loomans-Kropp; Zachariah H. Foda; Bryson W. Katona; Suzi Birz; Carol A. Burke; Jordan Clawson; Brian Furner; Camille Hochheimer; Elizabeth Magnan; Luigi Ricciardiello; Harminder Singh; et al. (Familial Cancer, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Plume-lithospheric mantle interaction for the origin of Archean mafic–ultramafic volcanics of the Prithvipur Greenstone Belt, Bundelkhand Craton, India: Geochemical and Sm Nd isotopic constraints - Balaram Sahoo; Pradip Kumar Singh; Ajay Kumar; Debajyoti Paul; Sanjeet Kumar Verma; Elson P. Oliveira; Torres Sánchez Darío; Dakshita; P.M. Ranjith (Geochemistry, 2026)

Evaluation of 1H-pyrazol-1-yl benzenesulfonamide derivatives in alleviating inflammatory bowel disease via PI3K/Akt/mTOR signaling pathway in zebrafish models - S. P. Ramya Ranjan Nayak; D. Priya; V. Chitra; Ajay Guru; Mohamed Farouk Elsadek; Mohamed S. Elshikh; Selvaraj Arokiyaraj; M. K. Kathiravan; Jesu Arockiaraj (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

New insights into the Neogene sedimentary Formations of south-western India: Implications for provenance, palaeovegetation and depositional environment - K.V. Sarath; K. Sandeep; Alka Absur; Namitha Ajay; Poonam Verma; Yogesh P. Singh; A.K. Rafaz; V. Nandakumar; G. Indu; E. Shaji (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Archean TTGs and high-K granitoids from the Madawara domain, Southern Bundelkhand Craton: Insights into petrogenesis, crustal growth, and mantle metasomatism - Pradip Kumar Singh; Ajay Kumar; Balaram Sahoo; Kumar Batuk Joshi; Sanjiv Kumar; Debajyoti Paul; Elson P. Oliveira; Dakshita; Vinod Kumar Singh; Arvind Kumar Gond; Archana Nikita Kispotta; Ishwar Chandra Rahi; et al. (Lithos, 2026)

Effects of an intervention for a liquefied petroleum gas cook-stove with free fuel on food insecurity and dietary diversity among women and infants: a multi-country randomized controlled trial - Sheela S. Sinharoy; Rina Das; Anaité Diaz-Artiga; Lisa M. Thompson; Ghislaine Rosa; John McCracken; Miles A. Kirby; Carla Tarazona-Meza; Vigneswari Aravindalochanan; Shirin Jabbarzadeh; Jiantong Wang; Ajay Pillarisetti; et al. (Food Security, 2026)

Therapeutic potential of Bergenia ciliata against lung cancer: an integrative molecular docking, ADMET, and molecular dynamics approach - Krittika Mukherjee; Sounok Sengupta; Ajay Kumar Singh; Rajiv Tonk; Shavkatjon Azizov; R. P. Rajwade; Deepak Kumar (In Silico Pharmacology, 2026)

Variability of Fine Particulate Matter (PM1.0 and PM2.5) and its Oxidative Potential at Different Locations in the Northern Part of India - Tulika Tripathi; Akshay Kale; Madhu Anand; P. G. Satsangi; Ajay Taneja (Aerosol Science and Engineering, 2025)

Household air pollution and blood pressure among adult women participants of the Household Air Pollution Intervention Network Trial: An exposure-response analysis - Ajay Pillarisetti; Wenlu Ye; Jennifer L. Peel; Howard Chang; Lindsay J. Underhill; Kalpana Balakrishnan; Anaité Díaz-Artiga; John P. McCracken; Ghislaine Rosa; Lisa M. Thompson; Vigneswari Aravindalochanan; Dana Boyd Barr; et al. (Environmental Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Effects of black soldier fly (Hermetia illucens) larvae meal as a partial substitute for soybean meal on growth performance, nutrient digestibility, blood constituents, carcass characteristics, intestinal morphology, and caecal microbiota in broiler chickens - Hardik P. Patel; Ajay P. Raval; Vipul R. Patel; Umed V. Ramani; Khushbu S. Rana (Tropical Animal Health and Production, 2025)

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Effect of on-tree storage on ripening related changes and sugar metabolism in fruits of different low-chill pear varieties - Akshita Jalota; Mandeep Singh; P. P. S. Gill; S. K. Grewal; Ajay Kamboj (Acta Physiologiae Plantarum, 2025)

Surface engineering of continuous flow microreactors via ALD: Design strategies and applications - Satchit Nagpal; Ajay Kumar Kalva; P. Aryan; Prasanth Syamala; I. Sreedhar; Neerugatti Krishna Rao Eswar; Satyapaul A. Singh (Journal of Environmental Chemical Engineering, 2025)

Variability and heritability for yield and yield attributing characters in an endangered medicinal herb Picrorhiza kurrooa Royle ex Benth under cultivation in Bharsar, Uttarakhand, Western Himalaya, India - Ajay Hemdan; Rajendra S. Chauhan; S. C. Pant; Hansveer Chahal; Prabhat Kumar; B. P. Nautiyal (Genetic Resources and Crop Evolution, 2025)

Advancements in Biomedical Sensors for Early Detection of Failure in Hip and Knee Implants: Scoping Review on Potential Sensors for Implant Integration - P. H. Helene Noordhuis; Paul C. Jutte; Ajay G. P. Kottapalli; Claudine J. C. Lamoth; C. C. Charissa Roossien (Annals of Biomedical Engineering, 2025)
Purpose Despite significant advancements in hip and knee joint implant technology, 6.4% of implants fail within the first ten years due to aseptic loosening, instability, and/or infection. Implants equipped with sensors show promise in early failure detection, enabling early and reduced intervention. This scoping review aims to provide an overview of biomedical sensors and their potential for integration into hip- and knee implants. Methods A comprehensive search of databases PubMed and Embase was performed. Inclusion criteria were sensors to detect failure causes infection, inflammation, loosening or wear; developed for biomedical applications; ex vivo, in vivo and/or in vitro studies. The sensors were analysed based on criteria per sensor characteristics (e.g. accuracy, durability, response time) relevant for implant integration. Results 49 articles were included presenting 52 sensors: 24 pressure and force, 6 strain, 15 acidity, 4 temperature, and 3 bacterial detection (3 dual sensing elements). Among these, three sensors were specifically designed for hip- and knee implants. The remaining 46 were developed for other biomedical applications. Our analysis identified two strain and seven acidity sensors that met the criteria for detecting hip- and knee implant failure. Two bacteria sensors showed potential for short-term use post-implantation, aligning with the critical period for periprosthetic infection, but the reporting frequency was too low to draw proper conclusions. No wear (particle) sensor was found. Conclusion We found a significant gap in sensors that can detect wear particles. Future work on continuous implant monitoring should focus on reducing risk and the enhancement of sensor durability and longevity.

Household air pollution exposure in adult women is associated with increased carotid intima-media thickness: A cross-sectional study of the Household Air Pollution Intervention Network trial. - Lindsay J. Underhill; Lisa de las Fuentes; Laura Nicolaou; Shakir Hossen; Anaite Diaz-Artiga; Ajay Pillarisetti; Aris T. Papageorghiou; Florien Ndagijimana; Ghislaine Rosa; Gurusamy Thangavel; John P. McCracken; Kalpana Balakrishnan; et al. (International Journal of Hygiene and Environmental Health, 2025)

First report of Microdochium fisheri associated with the glume discoloration disease of rice, Oryza sativa L. in India - P. K. Amrith; M. Surendran; B. Ajay; Susha S. Thara; T. Anuradha (Indian Phytopathology, 2025)

Efficacy of 6-nitrobenzo[d]thiazol-2 Amine Derivative (N3) in Mitigating PTZ-Induced Epileptic Conditions Via Modulation of Inflammatory and Neuroprotective Pathways in-vivo Zebrafish - Karthikeyan Ramamurthy; S. P. Ramya Ranjan Nayak; S. Madesh; Siva Prasad Panda; K. Manikandan; Rajakrishnan Rajagopal; Ahmed Alfarhan; Senthilkumar Palaniappan; Ajay Guru; M. K. Kathiravan; Jesu Arockiaraj (Journal of Neuroimmune Pharmacology, 2025)

Bacillus licheniformis and commercial fungicides exhibit high potential against major pathogens inciting grain discolouration disease in rice, Oryza sativa L. - P. K. Amrith; M. Surendran; N. V. Radhakrishnan; Susha S. Thara; T. Anuradha; B. Ajay (Indian Phytopathology, 2025)

Health risk assessment and morphometric study of metal bounded ultrafine aerosol in indo-gangetic plain, India - Rahul Tiwari; Kalpana Rajouriya; Renuka Saini; Prabal P. Singh; Ajay Taneja (Journal of Atmospheric Chemistry, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Protective Effect of Artemisinin Against Luperox Induced Oxidative Stress and Insulin Resistance via Pi3k/Akt Pathway in Zebrafish Larvae - Kadhirmathiyan Velumani; P. Sundar Rajan; Mohammed Rafi Shaik; Shaik Althaf Hussain; Baji Shaik; Ajay Guru; Praveen Kumar Issac (Cell Biochemistry and Biophysics, 2025)

Integration of Mycorrhizae, Azotobacter and Pseudomonas spp (PSB) with NPK and their Effects on Sugarcane Crop and Soil Health in Uttar Pradesh, India - M. K. Tripathi; S. K. Shukla; V. P. Jaiswal; Lalan Sharma; Mona Nagargade; A. D. Pathak; A. P. Dwivedi; Ankur Tripathi; V. K. Singh; V. P. Singh; Ajay Ranka (Sugar Tech, 2025)

Comprehensive analysis of seismic ambient noise in the Indian subcontinent - Gyanasmita Pradhan; Ramakrushna Reddy; P N S Roy; Om Prakash Mishra; Ajay Pratap Singh (Journal of Earth System Science, 2025)

An Insight Into Unveiling Nano Luminescence for Industrial Dye Detection - E. Safamariyam; K. P. Synumol; Anu Jayanthi Panicker; Mizaj Shabil Sha; Shabnam Roshan; Sarada Prasad Dakua; Vaisali Chandrasekar; Ajay Vikram Singh; Kishor Kumar Sadasivuni (Journal of Fluorescence, 2025)
Dye, a major contaminant from the textile, paper, and pulp industries, is a serious environmental and human health hazard. Because of their low cost, environmental friendliness, and sustainability, semiconductor nanoparticles are among the most effective photocatalysts for detecting dyes in wastewater. Quantum dots (QDs), particularly Carbon quantum dots (CQDs), have received a lot of attention due to their unique optical and electrical properties, making them excellent for applications such as sensing and detection. This paper describes a unique microwave-assisted method for synthesising CQDs in ambient reaction conditions, providing a fast, scalable, and passivation-free alternative to traditional methods. The CQDs were characterised using SEM, XRD, FTIR, UV–Vis spectrophotometry, and photoluminescence, which confirmed their uniform size distribution and outstanding optical characteristics. The CQDs had detection limits of 0.413 ppm for cresol red and 0.847 ppm for cresol purple, indicating great sensitivity and selectivity over a wide pH range. These findings propose a new, sustainable, and cost-effective alternative for tackling water pollution and its detrimental effects on aquatic ecosystems, hence increasing the use of Carbon QDs in environmental restoration.

Exploring the antidiabetic activity of potential probiotic bacteria isolated from traditional fermented beverage - Bishwapriya Chutia; Partha P. Dutta; Lunasmrita Saikia; Purvita Chowdhury; Munmi Borah; Dharmeswar Barhoi; Rupesh Kumar; Siddhartha N. Borah; Debajit Borah; Ajay Kumar Manhar; Manabendra Mandal; Bhaskarjyoti Gogoi (World Journal of Microbiology and Biotechnology, 2025)

A methodology for the mapping of acoustic impedance and porosity in the inter-well region using seismic inversion based on the Hooke and Jeeves algorithm - Ravi Kant; Brijesh Kumar; S. P. Maurya; Ajay P. Singh; G. Hema; Raghav Singh (Arabian Journal of Geosciences, 2025)

Retraction notice to “Combined effects of a high-fat diet and polyethylene microplastic exposure induce impaired lipid metabolism and locomotor behavior in larvae and adult zebrafish” [Sci. Total Environ. 902 (2023) 165988] - Seenivasan Boopathi; B. Haridevamuthu; Edrea Mendonca; Akash Gandhi; P. Snega Priya; Saad Alkahtani; Norah S. AL-Johani; Selvaraj Arokiyaraj; Ajay Guru; Jesu Arockiaraj; Guilherme Malafaia (Science of The Total Environment, 2024)

Transgenic tobacco plants overexpressing a wheat salt stress root protein (TaSSRP) exhibit enhanced tolerance to heat stress - Mawuli K. Azameti; N. Tanuja; Satish Kumar; Maniraj Rathinam; Abdul-Wahab M. Imoro; P. K. Singh; Kishor Gaikwad; Rohini Sreevathsa; Monika Dalal; Ajay Arora; Vandna Rai; Jasdeep C. Padaria (Molecular Biology Reports, 2024)

A combinational threat of micro- and nano-plastics (MNPs) as potential emerging vectors for per- and polyfluoroalkyl substances (PFAS) to human health - Sanjai Dharshan Santhanam; Karthikeyan Ramamurthy; P. Snega Priya; Gokul Sudhakaran; Ajay Guru; Jesu Arockiaraj (Environmental Monitoring and Assessment, 2024)

Influence of microorganisms on thermal conductivity of soils and its potential impact on soil aggregation - Manish V. Shah; Payal Tandel; Avadhi Patel; Ajay Chavda; Shalini Singh; Rakesh K. Panchal; Vijay Upadhye; Varsha K. Singh; Rajeshwar P. Sinha (Vegetos, 2024)

Identification of the reservoir using seismic inversion based on particle swarm optimization method: A case study - Ravi Kant; Brijesh Kumar; S P Maurya; Nitin Verma; Ajay P Singh; G Hema; Raghav Singh; K H Singh; Piyush Sarkar (Journal of Earth System Science, 2024)

Impact of acidic and alkaline conditions on Staphylococcus aureus and Acinetobacter baumannii interactions and their biofilms - Suthi Subbarayudu; P Snega priya; Rajakrishnan Rajagopal; Ahmed Alfarhan; Ajay Guru; Jesu Arockiaraj (Archives of Microbiology, 2024)

Himalayan type strongly peraluminous leucogranite from the western Madurai block, Southern Granulite Terrane, India: Evidence for Tonian crustal reworking - K Anto-Francis; J K Tomson; J Amal Dev; Anjitha Joseph; K P Sarathlal; K K Ajay; P G Dilipkumar (Journal of Earth System Science, 2024)

Enhancement of CO2 monitoring in the sleipner field (north sea) using seismic inversion based on simulated annealing of time-lapse seismic data - G. Hema; S.P. Maurya; Ravi Kant; Ajay P. Singh; Nitin Verma; Raghav Singh; K.H. Singh (Marine and Petroleum Geology, 2024)

A flowchart for porosity and acoustic impedance mapping using seismic inversion with semi hybrid optimization combining simulated annealing and pattern search techniques - Raghav Singh; S. P. Maurya; Brijesh Kumar; Nitin Verma; Alok Kumar Tiwari; Ravikant Tiwari; G. Hema; Ajay P. Singh (Marine Geophysical Research, 2024)

Revolutionizing Veterinary Health with Viral Vector-Based Vaccines - Harsh Rajeshbhai Jogi; Nabaneeta Smaraki; Kaushal Kishor Rajak; Ajay Kumar Yadav; Mukesh Bhatt; Chris Einstien; Annepu Revathi; Ravi Thakur; Dhaval J. Kamothi; P. V. S. S. Dedeepya; H. H. Savsani (Indian Journal of Microbiology, 2024)

Role of landslide sampling strategies in susceptibility modelling: types, comparison and mechanism - Jiyadh Thanveer; Ajay Singh; Amit V. Shirke; Bhavana Umrikar; Ali P. Yunus (Bulletin of Engineering Geology and the Environment, 2024)

Correlation of udder thermogram and somatic cell counts as a tool for detection of subclinical mastitis in buffaloes - Priyanka M. Kittur; Lija Satheesan; A. P. Madhusoodan; Karpenahalli Ranganatha Sriranga; Dheeraj Kumar; Aarti Kamboj; Ajay Kumar Dang (Veterinary Research Communications, 2024)

Textile azo dye, Sudan Black B, inducing hepatotoxicity demonstrated in in vivo zebrafish larval model - Karthikeyan Ramamurthy; Selvam Madesh; P. Snega Priya; Rashid Ayub; Hossam M. Aljawdah; Selvaraj Arokiyaraj; Ajay Guru; Jesu Arockiaraj (Fish Physiology and Biochemistry, 2024)

Unveiling carcinogenic pollutant levels in environmental water samples through facile fabrication of gold nanoparticles on sulfur-doped graphitic carbon nitride - N.S.K. Gowthaman; P. Arul; Ajay Ajith; Wei Sea Chang; Vellaichamy Balakumar; Jae-Jin Shim (Environmental Research, 2024)

RETRACTED: Mechanistic interplay of dual environmental stressors: Bisphenol-A and cadmium-induced ovarian follicular damage and hepatocyte dysfunction in vivo - Gokul Sudhakaran; P. Snega Priya; B. Haridevamuthu; Raghul Murugan; Jagan Kannan; Mikhlid H. Almutairi; Bader O. Almutairi; Ajay Guru; Jesu Arockiaraj (Science of The Total Environment, 2024)

Plant based surfactant combined sonication pretreatment on food waste for biomethane generation: Cost and energy procurement - K. Ajay Krishna Dev; Preethi; P. Rajaguru; M. Gunasekaran; J. Rajesh Banu (Fuel, 2024)

Effects of a liquefied petroleum gas stove intervention on stillbirth, congenital anomalies and neonatal mortality: A multi-country household air pollution intervention network trial - Ashley Younger; Wenlu Ye; Abbey Alkon; Kristen Harknett; Miles A. Kirby; Lisa Elon; Amy E. Lovvorn; Jiantong Wang; Anaité Diaz-Artiga; John P. McCracken; Adly Castañaza Gonzalez; Libny Monroy Alarcon; et al. (Environmental Pollution, 2024)

Integrated thin layer classification and reservoir characterization using sparse layer reflectivity inversion and radial basis function neural network: a case study - Raghav Singh; Aditya Srivastava; Ravi Kant; S. P. Maurya; P. Mahadasu; Nitin Verma; G. Hema; P. K. Kushwaha; Richa; K. H. Singh; Ajay P. Singh; M. K. Srivastava; et al. (Marine Geophysical Research, 2024)

Exploring the Efficacy of Pellitorine as an Antiparasitic Agent Against Argulus: Impacts on Antioxidant Levels and Immune Responses in Goldfish (Carassius auratus) - Seenivasan Boopathi; D. Kesavan; Gokul Sudhakaran; P. Snega Priya; B. Haridevamuthu; M. Dhanaraj; S. Seetharaman; Bader O. Almutairi; Selvaraj Arokiyaraj; Ajay Guru; Jesu Arockiaraj (Acta Parasitologica, 2024)

RETRACTED: Combined effects of a high-fat diet and polyethylene microplastic exposure induce impaired lipid metabolism and locomotor behavior in larvae and adult zebrafish - Seenivasan Boopathi; B. Haridevamuthu; Edrea Mendonca; Akash Gandhi; P. Snega Priya; Saad Alkahtani; Norah S. AL-Johani; Selvaraj Arokiyaraj; Ajay Guru; Jesu Arockiaraj; Guilherme Malafaia (Science of The Total Environment, 2023)

Prediction of acoustic impedance and density porosity using seismic inversion, and geostatistical methods on Krishna Godavari basin, India: A case study - S.P. Maurya; Richa; K.H. Singh; P. Mahadasu; Ajay P. Singh; G. Hema; P.K. Kushwaha; Raghav Singh (Journal of Applied Geophysics, 2023)

Unraveling the prevalence of various signalling pathways in non-small-cell lung cancer: a review - Aathira Sujathan Nair; Ajay P. Jayan; K R Anandu; V N Saiprabha; Leena K. Pappachen (Molecular and Cellular Biochemistry, 2023)

Abandonment of fibreglass reinforced plastic fishing boats in Kerala, India, and chemical emissions arising from their burning - N. Manju Lekshmi; Sreejith S. Kumar; P. Muhamed Ashraf; K. A. Martin Xavier; K. P. Prathish; S. V. Ajay; Leela Edwin; Andrew Turner (Environmental Monitoring and Assessment, 2023)

The Effect of Skeletal Muscle-Pump on Blood Pressure and Postural Control in Parkinson's Disease - Rabie Fadil; Asenath X. A. Huether; Farshid Sadeghian; Ajay K. Verma; Andrew P. Blaber; Jau-Shin Lou; Kouhyar Tavakolian (Cardiovascular Engineering and Technology, 2023)

Dual metal ion (Fe3+ and As3+) sensing and cell bioimaging using fluorescent carbon quantum dots synthesised from Cynodon dactylon - Sweta Gurung; Neha; Nimmala Arun; Mayank Joshi; Tanya Jaiswal; Anand P. Pathak; Parimal Das; Amaresh Kumar Singh; Ajay Tripathi; Archana Tiwari (Chemosphere, 2023)

Development of a field-deployable analytical workflow for determining current status and indicative human health risks at a historic dl-POPs hotspot - Kirankumar P S; Sanath K; Ajay S V; Amala Varghese; Prathish K P (Environmental Pollution, 2023)

Synthesis of Ca–Fe-based heterogeneous catalyst from waste shells and their application for transesterification of Jatropha oil - Surbhi Semwal; Tirath Raj; Anil Kumar Patel; Ajay K. Arora; Rajendra P. Badoni; Reeta Rani Singhania (Systems Microbiology and Biomanufacturing, 2023)

Understanding the Interaction and Potential of Halophytes and Associated Microbiome for Bio-saline Agriculture - Kamlesh K. Meena; Utkarsh Bitla; Ajay M. Sorty; Satish Kumar; Shrvan Kumar; Goraksha C. Wakchaure; Dhananjaya P. Singh; Peter Stougaard; P. Suprasanna (Journal of Plant Growth Regulation, 2023)

Both biogenic and chemically synthesized metal sulfide nanoparticles induce oxidative stress and enhance lipid accumulation in Rhodococcus opacus - Manoj Kumar; Tanushree Paul; P. V. Ajay Kumar; G. Pugazhenthi; Kannan Pakshirajan (BioMetals, 2023)

Remote sensing the evolution of debris-covered Panchi Nala-A glacier, India (1971-2021) from satellites and Unmanned Aerial Vehicles - Siddhi Garg; P. J. Navinkumar; Ajay Godara; Rakesh Sahu; Dhiraj Kumar Singh; RAAJ Ramsankaran (Regional Environmental Change, 2023)

Consortium of Management Practices in Long-Run Improves Soil Fertility and Carbon Sequestration in Drylands of Semi-Arid Tropics - Girish Chander; Ajay Singh; Kumar Abbhishek; Anthony M. Whitbread; M. L. Jat; Melesse B. Mequanint; Thomas Falk; B. Nagaraju; Prasad J. Kamdi; P. Cuba; Roja Mandapati; G. V. Anupama (International Journal of Plant Production, 2023)

Geoheritage Sites in Kumaun Himalaya of Uttarakhand, India - Girish Ch Kothyari; P. D. Pant; Bahadur Singh Kotlia; Manish Mehta; Harshita Joshi; Dinesh S. Chauhan; Rakesh K Dumka; Khayingshing Luirei; Moulishree Joshi; Bhuvan K Tamta; Achla Joshi; Ajay Kumar Taloor; et al. (Geoheritage, 2023)

Mutation spectrum and enzyme profiling of G6PD deficiency in neonates of north India: a prospective study - Upasana Bhattacharyya; Preeti Deswal; Sunil Kumar Polipalli; Diksha Sharma; Manpreet Kaur; Madhulika Kabra; Neerja Gupta; Ramesh Agarwal; A. K. Deorari; V. K. Paul; Shevendru Roy; R. K. Sanjeev; et al. (Journal of Genetics, 2023)

Biomedical,clinical and environmental applications of platinum-based nanohybrids: An updated review - Sachin T. Yerpude; Ajay K. Potbhare; Pavan Bhilkar; Alok R. Rai; Raghvendra P. Singh; Ahmed A. Abdala; Rameshwar Adhikari; Rohit Sharma; Ratiram G. Chaudhary (Environmental Research, 2023)

Opportunities in Critical Rare Earth Metal Recycling Value Chains for Economic Growth with Sustainable Technological Innovations - Ajay B. Patil; Rudolf P. W. J. Struis; Christian Ludwig (Circular Economy and Sustainability, 2023)
Rare earth elements (REEs) are often referred to as the industrial vitamins and the key drivers of the industry 4.0 revolution. The current global supply chain of REEs for green and high-tech applications with more than 220 metric kilotons per year involves a huge environmental impact (backpack) as well as the piling up of radioactive by-products to about 1.5 times the amount of REEs produced. E-wastes and municipal solid waste streams are attractive secondary resources. The current opinion paper discusses the recycling of rare earth metals along the value chain with the opportunities and challenges associated with it. The way to mitigate the economic constraints has been pointed out in terms of competitive quality and recovery of the REEs when compared with the mineral exploration options in the market. It is also emphasised that the technical complexity, capital expenditures and operating expenses need to fit the economic boundary conditions to make the recycling viable. In future, the appropriate REE-rich feedstocks such as fluorescent lamp e-waste powders and magnets can be potential secondary sources of the critical raw materials necessary for the green transition. The success of the viable recycling approaches and technologies will largely depend on the public–private partnerships based on hybrid financing models and local know-how generation to compete with quasi-monopoly in the REE supply chains. However, to break the monopolies, it will not be sufficient to only recycle the REEs; it will also be relevant to diversify the industries that produce REE-containing goods from recycled waste streams.

Role and mechanistic actions of protein kinase inhibitors as an effective drug target for cancer and COVID - J. Narayanan; T. Tamilanban; P. Senthil Kumar; Ajay Guru; Saravanan Muthupandian; M. K. Kathiravan; Jesu Arockiaraj (Archives of Microbiology, 2023)

Tracing hydrothermal mineral thenardite in geysers/hot springs of North-western Himalayan belt, Ladakh Geothermal Province, India by hydrogeochemistry, fluid-mineral equilibria and isotopic studies - Archisman Dutta; Parashar Mishra; Ahsan Absar; Vivek P. Malviya; P.K. Singh; Ajay Srivastava; Biswajit Ray; Alok Kumar; N.V. Nitnaware (Geochemistry, 2023)

Recovery and purification of copper sulfide nanoparticles from acid mine drainage by biological sulfate reduction and microfiltration using low-cost ceramic membrane - Manoj Kumar; P. V. Ajay Kumar; G. Pugazhenthi; Kannan Pakshirajan (Clean Technologies and Environmental Policy, 2023)

Observations on the decadal variability of aerosol in eastern Himalayan foothills: Evidence of an anthropologically induced positive shift - Tamanna Subba; Binita Pathak; Mukunda M. Gogoi; P. Ajay; Papori Dahutia; Aniket Chakraborty; Pradip K. Bhuyan (Atmospheric Environment, 2023)

Syringol, a wildfire residual methoxyphenol causes cytotoxicity and teratogenicity in zebrafish model - P. Snega Priya; Ajay Guru; Ramu Meenatchi; B. Haridevamuthu; Manikandan Velayutham; Boopathi Seenivasan; Raman Pachaiappan; Rajakrishnan Rajagopal; Palaniselvam Kuppusamy; Annie Juliet; Jesu Arockiaraj (Science of The Total Environment, 2023)

Repeated assessment of PM2.5 in Guatemalan kitchens cooking with wood: Implications for measurement strategies - Ajay Pillarisetti; Line W.H. Alnes; Wenlu Ye; John P. McCracken; Eduardo Canuz; Kirk R. Smith (Atmospheric Environment, 2023)

The formaldehyde treated guar meal and prill fat, agro industrial by-products as dietary rumen protected protein and energy source: improves growth performance, feed conversion, nutrient utilization, microbial protein synthesis, blood metabolites and economic efficiency in growing dairy buffalo (Bubalus bubalis) calves - Abhishek B. Parmar; Dilip C. Patel; Nitesh P. Sarvaiya; Ajay P. Parmar; Arjun J. Dhami; Priya J. Ahir (Tropical Animal Health and Production, 2023)

Hydroxytriazenes incorporating sulphonamide derivatives: evaluation of antidiabetic, antioxidant, anti-inflammatory activities, and computational study - Laxmi K. Chauhan; Jaishri Chopra; Murugesan Vanangamudi; Indra P. Tripathi; Amit Bhargava; Ajay K. Goswami; Prabhat K. Baroliya (Molecular Diversity, 2023)

Long non‐coding RNA , a supreme post‐transcriptional immune regulator of bacterial or virus‐driven immune evolution in teleost - B. Haridevamuthu; Ajay Guru; Manikandan Velayutham; P. Snega Priya; Aziz Arshad; Jesu Arockiaraj (Reviews in Aquaculture, 2023)
The global aquaculture boom, fuelled by a reduction in wild population and detection of novel viruses, has created a demanding market, hence, there is a pressing need to investigate the immune system of fish, further. As the most diverse community of vertebrates and a central contributor to the progressing global aquaculture market, teleost continues to draw vast scientific interest. Recent breakthroughs in multi‐omics technologies have provided a platform to understand the role of long non‐coding RNA (lncRNA) in the host immune system during infection. Emerging evidence shows that teleost lncRNA might have a regulatory role in immune responses, mostly through lncRNA–microRNA (miRNA) sponging. Teleost lncRNA shares a functionally active short sequence complement to target the miRNA which is conserved among the several fish species. Recent report suggests that rhabdovirus exploits a lncRNA in teleost and, to dodge the host immune mechanism and negatively regulate the immune system. This observation reveals the essentiality of lncRNA in pathogen‐driven immunity in teleost. Reports available on the function of teleost lncRNA are still in early stages and experimental verifications are a limiting factor. Unravelling the lncRNA‐mediated immune regulation in fishes could be used against the invading pathogens to strengthen the aquaculture production. This review elaborates on the experimentally identified and functionally characterized lncRNA and its regulatory role in the teleost immune response during infection and pathogen‐driven host immune evolution, which could eventually lead to achieving high standards in aquaculture productivity.

Seasonal effects of atmospheric waves over tropical tropopause using radiosonde observations at Hyderabad, India - Salauddin Mohammad; Gopa Dutta; M. C. Ajay Kumar; P. V. Rao; P. Vinay Kumar; Krishna Ette (Meteorology and Atmospheric Physics, 2022)

Assessment of Dioxin-Like POP’s Emissions and Human Exposure Risk from Open Burning of Municipal Solid Wastes in Streets and Dumpyard Fire Breakouts - S. V. Ajay; P. S. Kirankumar; Amala Varghese; K. P. Prathish (Exposure and Health, 2022)

Applications of Sentinel-2 satellite data for spatio-temporal mapping of deep pools for monitoring the riverine connectivity and assessment of ecological dynamics: a case from Godavari, a tropical river in India (2016–2021) - G. Kantharajan; Arur Anand; P. Krishnan; Rajeev K. Singh; Kundan Kumar; Ajay Kumar Yadav; Vindhya Mohindra; S. P. Shukla; Kuldeep K. Lal (Environmental Monitoring and Assessment, 2022)

Experimental, computational analysis of Butein and Lanceoletin for natural dye-sensitized solar cells and stabilizing efficiency by IoT - M. Bradha; Nagaraj Balakrishnan; A. Suvitha; T. Arumanayagam; M. Rekha; P. Vivek; P. Ajay; V. Sangeetha; Ananth Steephen (Environment, Development and Sustainability, 2022)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

ThoraxNet: a 3D U-Net based two-stage framework for OAR segmentation on thoracic CT images - Seenia Francis; P. B. Jayaraj; P. N. Pournami; Manu Thomas; Ajay Thoomkuzhy Jose; Allen John Binu; Niyas Puzhakkal (Physical and Engineering Sciences in Medicine, 2022)

In Silico Studies and Design of Scrupulous Novel Sensor for Nitro Aromatics Compounds and Metal Ions Detection - Ajay L. Desai; Nihal P. Patel; Jaymin H. Parikh; Krunal M. Modi; Keyur D. Bhatt (Journal of Fluorescence, 2022)

Intelligent ecofriendly transport management system based on IoT in urban areas - P. Ajay; B. Nagaraj; Branesh Madhavan Pillai; Jackrit Suthakorn; M. Bradha (Environment, Development and Sustainability, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Systems-based rice improvement approaches for sustainable food and nutritional security - Vivek Verma; Bhushan Vishal; Ajay Kohli; Prakash P. Kumar (Plant Cell Reports, 2021)

Genetic determinants of micronutrient traits in graminaceous crops to combat hidden hunger - P. Sushree Shyamli; Sumi Rana; Sandhya Suranjika; Mehanathan Muthamilarasan; Ajay Parida; Manoj Prasad (Theoretical and Applied Genetics, 2021)

Natural mixed infections on Phalaenopsis species by groundnut bud necrosis orthotospovirus, cymbidium mosaic virus and odontoglossum ringspot virus in India - R. P. Pant; Y. B. Basavaraj; Nishant Srivastava; Ajay Bhattarai; Ashwini Kumar; V. K. Baranwal; N. Sailo; Rampal; D. Barman (Indian Phytopathology, 2021)

UAV-Based Survey of Glaciers in Himalayas: Challenges and Recommendations - RAAJ Ramsankaran; P. J. Navinkumar; Ajay Dashora; Anil V. Kulkarni (Journal of the Indian Society of Remote Sensing, 2021)

Functionalized Silver Nanoparticles as Colorimetric and Fluorimetric Sensor for Environmentally Toxic Mercury Ions: An Overview - Nandan C. Pomal; Keyur D. Bhatt; Krunal M. Modi; Ajay L. Desai; Nihal P. Patel; Anita Kongor; Viliam Kolivoška (Journal of Fluorescence, 2021)

Association of cucurbit aphid-borne yellows virus with cucumber plants in India - Ashwini Kumar; Ajay Bhattarai; Aayushi Singh Rathore; Gograj Singh Jat; Tusar Kanti Behera; P. Renukadevi; Virendra K. Baranwal; Rakesh Kumar Jain; Y. B. Basavaraj (VirusDisease, 2021)

Fatty acid desaturase-2 (ahFAD2) mutant alleles in peanut (Arachis hypogaea L.) pre-breeding lines: an insight into the source, features, discourse, and selection of novel pre-breeding lines - J. H. Kamdar; M. D. Jasani; B. C. Ajay; Kirti Rani; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; M. K. Pandey; P. Janila; T. Radhakrishnan; R. K. Varshney; S. K. Bera (Genetic Resources and Crop Evolution, 2021)

A facile synthesis of some new pyrimidine-2,4,6-triones analogs and their O-β-D-glucosides P-glycoprotein and antioxidant, antimicrobial study, blood–brain barrier, cytochrome p450 enzyme activity prediction - Kishor M. Hatzade; Ajay M. Ghatole; Pravin K. Gaidhane; Mahesh K. Gaidhane; Gunwant P. Gadekar (Medicinal Chemistry Research, 2021)

Genetic diversity in leafy mustard (Brassica juncea var. rugosa) as revealed by agro-morphological traits and SSR markers - Deepika Sharma; J. Nanjundan; Lal Singh; S. P. Singh; Nehanjali Parmar; M. S. Sujith Kumar; K. H. Singh; A. K. Mishra; Ranbir Singh; Kumar Sambhav Verma; Ajay Kumar Thakur (Physiology and Molecular Biology of Plants, 2020)

Correction to: Does climate change framing matter? Evidence from an experiment of crop advisors in the Midwestern United States - Ajay S. Singh; Sarah P. Church; Layla Dang; Erin P. Hennes; Linda S. Prokopy (Climatic Change, 2020)

Does climate change framing matter? Evidence from an experiment of crop advisors in the Midwestern United States - Ajay S. Singh; Sarah P. Church; Layla Dang; Erin P. Hennes; Linda S. Prokopy (Climatic Change, 2020)

Cannabis sativa L.: A Potential Natural Reservoir of Sugarcane Grassy Shoot Phytoplasmas in India - Renu Maurya; Smriti Mall; Ajay K. Tiwari; Vikash Jadon; Carmine Marcone; Govind P. Rao (Sugar Tech, 2020)

Effect of Cow Urine-Based Bioformulations on Growth and Physiological Responses in Mungbean Under Soil Moisture Stress Conditions - Jagadish Rane; Ajay Kumar Singh; Priya George; Venkadasamy Govindasamy; Abhishek Cukkemane; Susheel Kumar Raina; Madhuri P. Chavan; Lalitkumar Aher; V. S. John Sunoj; Narendra Pratap Singh (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Comparative analysis of chromosome 2A molecular organization in diploid and hexaploid wheat - Parampreet Kaur; Suruchi Jindal; Bharat Yadav; Inderjit Yadav; Ajay Mahato; Priti Sharma; Satinder Kaur; O. P. Gupta; Jan Vrána; Hana Šimková; Jaroslav Doležel; Bikram Singh Gill; et al. (Molecular Biology Reports, 2020)

Novel candidates in early-onset familial colorectal cancer - Anne M. L. Jansen; Pradipta Ghosh; Tikam C. Dakal; Thomas P. Slavin; C. Richard Boland; Ajay Goel (Familial Cancer, 2020)

Stack emissions and health risk integrated (SEHRI) model: a tool for stack emissions and health risk modeling - Pralhad P. Walvekar; Bhola R. Gurjar; Ajay Singh Nagpure (Air Quality, Atmosphere & Health, 2019)

Genome-wide integrated analysis of miRNA and mRNA expression profiles to identify differentially expressed miR-22-5p and miR-27b-5p in response to classical swine fever vaccine virus - Lalrengpuii Sailo; Amit Kumar; Vaishali Sah; Rajni Chaudhary; Vikramaditya Upmanyu; A. K. Tiwari; Ajay Kumar; Aruna Pandey; Shikha Saxena; Akansha Singh; Sajad Ahmad Wani; Ravi Kumar Gandham; et al. (Functional & Integrative Genomics, 2019)

Impact of microphysics parameterizations and horizontal resolutions on simulation of “MORA” tropical cyclone over Bay of Bengal using Numerical Weather Prediction Model - Lakhima Chutia; Binita Pathak; Ajay Parottil; P. K. Bhuyan (Meteorology and Atmospheric Physics, 2019)

Expression and characterization of the non-structural protein V of small ruminant morbillivirus - Ajay Kumar Yadav; Dheeraj Chaudhary; Sakshi Bhadouriya; S. Chandrasekar; V. V. Dhanesh; Kaushal K. Rajak; R. P. Singh; M. A. Ramakrishnan; R. K. Singh; Dhanavelu Muthuchelvan (VirusDisease, 2019)

Obtaining best parameterization scheme of RegCM 4.4 for aerosols and chemistry simulations over the CORDEX South Asia - P. Ajay; B. Pathak; F. Solmon; P. K. Bhuyan; F. Giorgi (Climate Dynamics, 2019)

Role of formalin fixed paraffin embedded liver tissues in the diagnosis of viral hepatitis E in patients with undiagnosed acute liver failure - Radha Kanta Ratho; Vikram Thakur; Manasi Majumdar; Mini P. Singh; Ashim Das; Ajay Duseja; Jasmine Khurana (VirusDisease, 2019)

Endotoxin exposures during harvesting and processing cannabis at an outdoor cannabis farm - James R. Couch; Nancy C. Burton; Kerton R. Victory; Brett J. Green; Angela R. Lemons; Ajay P. Nayak; Donald H. Beezhold (Aerobiologia, 2019)

Multienvironmental evaluation of wheat (Triticum aestivum L.) germplasm identifies donors with multiple fungal disease resistance - Satish Kumar; Garima Singroha; S. C. Bhardwaj; Ritu Bala; M. S. Saharan; Vikas Gupta; Anwar Khan; Sunita Mahapatra; M. Sivasamy; Vijay Rana; C. N. Mishra; Om Prakash; et al. (Genetic Resources and Crop Evolution, 2019)

In silico annotation of 458 genes identified from comparative analysis of Full length cDNAs and NextGen Sequence of chromosome 2A of hexaploid wheat - Parampreet Kaur; Inderjit Singh Yadav; Bharat Yadav; Ajay Mahato; O. P. Gupta; J. Dolezel; Nagendra Kumar Singh; J. P. Khurana; Kuldeep Singh (Journal of Plant Biochemistry and Biotechnology, 2019)

Improving oil quality by altering levels of fatty acids through marker-assisted selection of ahfad2 alleles in peanut (Arachis hypogaea L.) - Sandip K. Bera; Jignesh H. Kamdar; Swati V. Kasundra; Pitabas Dash; Anil K. Maurya; Mital D. Jasani; Ajay B. Chandrashekar; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; Manish K. Pandey; Pasupuleti Janila; et al. (Euphytica, 2018)

Ultrasonic P- and S-Wave Attenuation and Petrophysical Properties of Deccan Flood Basalts, India, as Revealed by Borehole Studies - Nimisha Vedanti; Ajay Malkoti; O. P. Pandey; J. P. Shrivastava (Pure and Applied Geophysics, 2018)

Biological degradation of toluene by indigenous bacteria Acinetobacter junii CH005 isolated from petroleum contaminated sites in India - Pardeep Singh; Vipin Kumar Singh; Rishikesh Singh; Anwesha Borthakur; Ajay Kumar; Dhanesh Tiwary; P. K. Mishra (Energy, Ecology and Environment, 2018)

Climatic variability of the Pacific and Atlantic Oceans and western US snowpack - Pratik Pathak; Ajay Kalra; Kenneth W. Lamb; William P. Miller; Sajjad Ahmad; Rajesh Amerineni; Devi P. Ponugoti (International Journal of Climatology, 2018)
This study examines the changing characteristics of snow water equivalent (SWE) in western United States and their teleconnections with large‐scale variability of the Pacific and Atlantic Oceans. This study evaluated the relationship among sea surface temperatures (SST), 500‐mbar geopotential height (Z 500 ), 500‐mbar east–west wind (U 500 ), and western United States SWE (1 March, 1 April, and 1 May). The averages of SST, Z 500 , and U 500 were computed to create a lead time of 2–10 months. Three different 6‐month series were computed – January–June, April–September, and July–December – and were correlated with SWE stations in the western United States. The study utilized singular‐value decomposition (SVD) for a period of 1961–2016 to correlate the SWE and climate indices. SVD was applied between the standardized SST and SWE to obtain their correlation and to evaluate connection with Z 500 and U 500 within the same SVD relationship. Specifically, SVD was not applied independently on each variable prior to this study. The correlations were observed to increase as the lead time decreased. First mode SVD showed a pronounced non‐El Niño‐Southern Oscillation short‐wave train for the July–December climate in the Z 500 data; this terminated over the Great Lakes region, and was strongly correlated with the warming of the SST near the east coast of Japan, resulting in decreased SWE in the study area. Second mode SVD showed a negative correlation between SWE stations in Colorado and Utah and SST near the Asian and Australian continents. The associations between climate indices and SWE that were identified during this study could be used to improve long‐term forecasts, resulting in better management of water resources in the region.

Accurate lumen diameter measurement in curved vessels in carotid ultrasound: an iterative scale-space and spatial transformation approach - P. Krishna Kumar; Tadashi Araki; Jeny Rajan; Luca Saba; Francesco Lavra; Nobutaka Ikeda; Aditya M. Sharma; Shoaib Shafique; Andrew Nicolaides; John R. Laird; Ajay Gupta; Jasjit S. Suri (Medical & Biological Engineering & Computing, 2017)

SCMR: A More Pertinent Trait than SLA in Peanut Genotypes Under Transient Water Deficit Stress During Summer - K. A. Kalariya; A. L. Singh; K. Chakraborty; B. C. Ajay; P. V. Zala; C. B. Patel; R. N. Nakar; Nisha Goswami; Deepti Mehta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Identification and characterization of two phytoplasma subgroups (16SrXI-D and 16SrXIV-A) associated with lychee (Litchi chinensis Sonn) in India - Govind P. Rao; Ajay K. Tiwari; Madhupriya; Durgesh Dubey (Journal of Plant Diseases and Protection, 2017)

Site-Specific Fertilizer Nitrogen Management Using Optical Sensor in Irrigated Wheat in the Northwestern India - Bijay-Singh; Varinderpal-Singh; Yadvinder-Singh; H. S. Thind; Ajay Kumar; O. P. Choudhary; R. K. Gupta; Monika Vashistha (Agricultural Research, 2017)

New Efficient Natural Leafhopper Vectors of Sugarcane Grassy Shoot Phytoplasma in India - Ajay K. Tiwari; Shailender Kumar; Smriti Mall; Vikas Jadon; Govind P. Rao (Sugar Tech, 2017)

Cyanobacterial (unicellular and heterocystous) biofertilization to wetland rice influenced by nitrogenous agrochemical - N. P. Dash; Ajay Kumar; Manish Singh Kaushik; Pawan Kumar Singh (Journal of Applied Phycology, 2016)

Efavirenz Self-Nano-Emulsifying Drug Delivery System: In Vitro and In Vivo Evaluation - Ravindra N. Kamble; Piyush P. Mehta; Ajay Kumar (AAPS PharmSciTech, 2016)

Evaluation of Ascorbic Acid and Sodium Metabisulfite Applications for Improvement in Raisin Quality - Ajay Kumar Sharma; K. Banerjee; S. D. Ramteke; Satisha Jogaiah; R. G. Somkuwar; P. G. Adsule (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Incidence of mastitis and activity of milk neutrophils in Tharparkar cows reared under semi-arid conditions - Mohanned Alhussien; P. Manjari; Seid Mohammed; Aasif Ahmad Sheikh; Srinu Reddi; Satpal Dixit; Ajay K. Dang (Tropical Animal Health and Production, 2016)

Sediment accumulation and bio-diffusion mixing rates derived from excess 210Pb and 137Cs profiles in sediment cores of Mumbai Harbor Bay - Ajay Kumar; Sabyasachi Rout; R. K. Singhal; P. M. Ravi; R. M. Tripathi (Journal of Coastal Conservation, 2016)

Novel Method to Track Soft Tissue Deformation by Micro-Computed Tomography: Application to the Mitral Valve - Eric L. Pierce; Charles H. Bloodworth; Ajay Naran; Thomas F. Easley; Morten O. Jensen; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2016)

Bovine Herpes Virus 1 Major Immediate Early Transcription Unit 1 (IETU-1) Uses Alternative Promoters to Transcribe BICP0 and BICP4 Transcripts - Mayank Pokhriyal; O. P. Verma; Barkha Ratta; Ajay Kumar; Meeta Saxena; Bhaskar Sharma (Current Microbiology, 2016)

Assessment of terminal heat tolerance ability of wheat genotypes based on physiological traits using multivariate analysis - Shivani Nagar; V. P. Singh; Ajay Arora; Rajkumar Dhakar; Shiv Ramakrishnan (Acta Physiologiae Plantarum, 2015)

Site-specific fertilizer nitrogen management in irrigated transplanted rice (Oryza sativa) using an optical sensor - Bijay-Singh; Varinderpal-Singh; Jaspreet Purba; R. K. Sharma; M. L. Jat; Yadvinder-Singh; H. S. Thind; R. K. Gupta; O. P. Chaudhary; P. Chandna; H. S. Khurana; Ajay Kumar; et al. (Precision Agriculture, 2015)

Photosynthetic characteristics of peanut genotypes under excess and deficit irrigation during summer - Kuldeepsingh A. Kalariya; Amrit Lal Singh; Nisha Goswami; Deepti Mehta; Mahesh Kumar Mahatma; B. C. Ajay; Koushik Chakraborty; P. V. Zala; Vidya Chaudhary; C. B. Patel (Physiology and Molecular Biology of Plants, 2015)

Malus pumila ‘Spy 227’ and Apple stem pitting virus: graft incompatibility and epinasty - Ajay Brakta; Anil Handa; P. D. Thakur; Manica Tomar; Pardeep Kumar (VirusDisease, 2015)

Characterization of a 16SrI-B Subgroup Phytoplasma Associated with Sugarcane Leaf Yellows Disease in India - Shailender Kumar; Ajay K. Tiwari; Somnath K. Holkar; S. K. Duttamajumder; G. P. Rao (Sugar Tech, 2015)

Cyanobacteria, pesticides and rice interaction - N. P. Das; Ajay Kumar; P. K. Singh (Biodiversity and Conservation, 2015)

clpC operon regulates cell architecture and sporulation in Bacillus anthracis - Lalit K. Singh; Neha Dhasmana; Andaleeb Sajid; Prasun Kumar; Asani Bhaduri; Mitasha Bharadwaj; Sheetal Gandotra; Vipin C. Kalia; Taposh K. Das; Ajay K. Goel; Andrei P. Pomerantsev; Richa Misra; et al. (Environmental Microbiology, 2015)
Summary The clpC operon is known to regulate several processes such as genetic competence, protein degradation and stress survival in bacteria. Here, we describe the role of clpC operon in B acillus anthracis . We generated knockout strains of the clpC operon genes to investigate the impact of CtsR , McsA , McsB and ClpC deletion on essential processes of B . anthracis. We observed that growth, cell division, sporulation and germination were severely affected in mcsB and clpC deleted strains, while none of deletions affected toxin secretion. Growth defect in these strains was pronounced at elevated temperature. The growth pattern gets restored on complementation of mcsB and clpC in respective mutants. Electron microscopic examination revealed that mcsB and clpC deletion also causes defect in septum formation leading to cell elongation. These vegetative cell deformities were accompanied by inability of mutant strains to generate morphologically intact spores. Higher levels of polyhydroxybutyrate granules accumulation were also observed in these deletion strains, indicating a defect in sporulation process. Our results demonstrate, for the first time, the vital role played by McsB and ClpC in physiology of B . anthracis and open up further interest on this operon, which might be of importance to success of B . anthracis as pathogen.

Dissipation pattern, safety evaluation, and generation of processing factor (PF) for pyraclostrobin and metiram residues in grapes during raisin preparation - Ahammed Shabeer T. P.; Rushali Girame; Sandip Hingmire; Kaushik Banerjee; Ajay Kumar Sharma; Dasharath Oulkar; Sagar Utture; Manjusha Jadhav (Environmental Monitoring and Assessment, 2015)

Exploitation of microbes for enhancing bacoside content and reduction of Meloidogyne incognita infestation in Bacopa monnieri L - Rupali Gupta; Sudeep Tiwari; Shilpi K. Saikia; Virendra Shukla; Rashmi Singh; S. P. Singh; P. V. Ajay Kumar; Rakesh Pandey (Protoplasma, 2015)

Sources and characteristics of carbonaceous aerosols at Agra “World heritage site” and Delhi “capital city of India” - A. S. Pipal; S. Tiwari; P. G. Satsangi; Ajay Taneja; D.S. Bisht; A. K. Srivastava; M. K. Srivastava (Environmental Science and Pollution Research, 2014)

Natural variation in the regulation of leaf senescence and relation to N and root traits in wheat - K. B. Hebbar; J. Rane; S. Ramana; N. R. Panwar; S. Ajay; A. Subba Rao; P. V. V. Prasad (Plant and Soil, 2014)

First results from imaging riometer installed at Indian Antarctic station Maitri - JAYANTA K BEHERA; A K SINHA; ANAND K SINGH; RAHUL RAWAT; GEETA VICHARE; AJAY DHAR; B M PATHAN; K U NAIR; C SELVARAJ; P ELANGO (Journal of Earth System Science, 2014)

Developmental potency of pre-implant parthenogenetic goat embryos: effect of activation protocols and culture media - Dharmendra Kumar; R. Gopalakrishna; Ajay P. Singh; Rakesh Ranjan; Saurabh K. Pandey; Bikash C. Sarkhel (In Vitro Cellular & Developmental Biology - Animal, 2014)

The role of abscisic acid (ABA) in ethylene insensitive Gladiolus (Gladiolus grandiflora Hort.) flower senescence - Madan Kumar; V. P. Singh; Ajay Arora; Neera Singh (Acta Physiologiae Plantarum, 2014)

The specific degree-of-polymerization of A-type proanthocyanidin oligomers impacts Streptococcus mutans glucan-mediated adhesion and transcriptome responses within biofilms - Guoping Feng; Marlise I. Klein; Stacy Gregoire; Ajay P. Singh; Nicholi Vorsa; Hyun Koo (Biofouling, 2013)

The phytohormone crosstalk paradigm takes center stage in understanding how plants respond to abiotic stresses - Ajay Kohli; Nese Sreenivasulu; Prakash Lakshmanan; Prakash P. Kumar (Plant Cell Reports, 2013)

Field application uniformity and accuracy of two rate control systems with automatic section capabilities on agricultural sprayers - Ajay Sharda; Joe D. Luck; John P. Fulton; Timothy P. McDonald; Scott A. Shearer (Precision Agriculture, 2013)

Substrate utilization of stress tolerant methylotrophs isolated from revegetated heavy metal polluted coalmine spoil - D. D. Giri; P. N. Shukla; Singh Ritu; Ajay Kumar; K. D. Pandey (World Journal of Microbiology and Biotechnology, 2013)

Supplementing Fertilizer Nitrogen Application to Irrigated Wheat at Maximum Tillering Stage Using Chlorophyll Meter and Optical Sensor - Bijay-Singh; Varinderpal-Singh; Yadvinder-Singh; H. S. Thind; Ajay-Kumar; Satinderpal-Singh; O. P. Choudhary; R. K. Gupta; Monika Vashistha (Agricultural Research, 2013)

Dosing of adult pigeons with as little as one #9 lead pellet caused severe δ-ALAD depression, suggesting potential adverse effects in wild populations - Jeremy P. Holladay; Mandy Nisanian; Susan Williams; R. Cary Tuckfield; Richard Kerr; Timothy Jarrett; Lawrence Tannenbaum; Steven D. Holladay; Ajay Sharma; Robert M. Gogal (Ecotoxicology, 2012)

Genetic analysis of yield and quantitative traits in pigeonpea (Cajanus cajan L. Millsp.) - B. C. Ajay; B. N. Gnanesh; K. N. Ganapathy; M. Byre Gowda; P. S. Prasad; G. N. Veerakumar; S. C. Venkatesha; R. Abdul Fiyaz; K. T. Ramya (Euphytica, 2012)

Accessing a small library of pluripotent 1,4,5-trisubstituted 1H-1,2,3-triazoles via diversity-oriented synthesis - Arya Ajay; Munna Prasad Gupt; N. Devender; Rama P. Tripathi (Molecular Diversity, 2012)

The first draft of the pigeonpea genome sequence - Nagendra K. Singh; Deepak K. Gupta; Pawan K. Jayaswal; Ajay K. Mahato; Sutapa Dutta; Sangeeta Singh; Shefali Bhutani; Vivek Dogra; Bikram P. Singh; Giriraj Kumawat; Jitendra K. Pal; Awadhesh Pandit; et al. (Journal of Plant Biochemistry and Biotechnology, 2012)

Characterization of Recombinant Terrelysin, a Hemolysin of Aspergillus terreus - Ajay P. Nayak; Françoise M. Blachere; Justin M. Hettick; Slawomir Lukomski; Detlef Schmechel; Donald H. Beezhold (Mycopathologia, 2011)

Influence of cellular differentiation and elicitation on intermediate and late steps of terpenoid indole alkaloid biosynthesis in Catharanthus roseus - Ashutosh K. Shukla; Ajit K. Shasany; Ram K. Verma; Madan M. Gupta; Ajay K. Mathur; Suman P. S. Khanuja (Protoplasma, 2010)

Relative performance of neem (Azadirachta indica) coated urea vis-à-vis ordinary urea applied to rice on the basis of soil test or following need based nitrogen management using leaf colour chart - H. S. Thind; Bijay-Singh; R. P. S. Pannu; Yadvinder-Singh; Varinderpal-Singh; R. K. Gupta; Monika Vashistha; Jagmohan Singh; Ajay Kumar (Nutrient Cycling in Agroecosystems, 2010)

RT-PCR/PCR analysis detected mixed infection of DNA and RNA viruses infecting sugarcane crops in different states of India - Deepti Singh; Ajay K. Tewari; G. P. Rao; R. Karuppaiah; R. Viswanathan; Meenakshi Arya; V. K. Baranwal (Sugar Tech, 2009)

Comparative study of a Zn-enriched post-methanation bio-sludge and Zn sulfate as Zn sources for a rice–wheat crop rotation - Prakash C. Srivastava; Ajay P. Singh; Surendra Kumar; V. Ramachandran; Manoj Shrivastava; S. F. D’souza (Nutrient Cycling in Agroecosystems, 2009)

Impact of recurring intermediate insulin-induced hypoglycemia on hypothalamic paraventricular corticotropin-releasing hormone, oxytocin, vasopressin and glucokinase gene profiles: role of type II glucocorticoid receptors - Karen P. Briski; Ajay Y. Kale; Kamlesh V. Vavaiya (Experimental Brain Research, 2009)

Desorption and transformation of zinc in a mollisol and its uptake by plants in a rice–wheat rotation fertilized with either zinc-enriched biosludge from molasses or with inorganic zinc - Prakash C. Srivastava; Ajay P. Singh; Surendra Kumar; V. Ramachandran; Manoj Shrivastava; S. F. D’souza (Biology and Fertility of Soils, 2008)

Relationships of Heavy Metals in Natural Lake Waters with Physico-chemical Characteristics of Waters and Different Chemical Fractions of Metals in Sediments - Ajay P. Singh; Prakash C. Srivastava; Prashant Srivastava (Water, Air, & Soil Pollution, 2008)

Species Status and Relationship Between Roccella montagnei and Roccella belangeriana Using DNA Sequence Data of Nuclear Ribosomal Internal Transcribed Spacer Region - S. R. Prashanth; P. Bharath; R. Valarmathi; P. Balaji; Ajay Parida; G. N. Hariharan (Journal of Plant Biochemistry and Biotechnology, 2008)

Progress in the CFD Modeling of Flow Instabilities in Anatomical Total Cavopulmonary Connections - Chang Wang; Kerem Pekkan; Diane de Zélicourt; Marc Horner; Ajay Parihar; Ashish Kulkarni; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2007)

Targeted Sialic Acid–Doxorubicin Prodrugs for Intracellular Delivery and Cancer Treatment - Sreeja Jayant; Jayant J. Khandare; Yang Wang; Ajay P. Singh; Nicholi Vorsa; Tamara Minko (Pharmaceutical Research, 2007)

Effects of topical administration of 12-methyl tetradecanoic acid (12-MTA) on the development of corneal angiogenesis - Nerida Cole; Emma B. H. Hume; Isabelle Jalbert; Ajay Kumar Vijay; Ravi Krishnan; Mark D. P. Willcox (Angiogenesis, 2007)

Site-specific habituation of insulin-induced hypoglycemic induction of Fos immunoreactivity in glucocorticoid receptor: immunopositive neurons in the male rat brain - Ajay Y. Kale; Sachin A. Paranjape; Karen P. Briski (Experimental Brain Research, 2007)

Trinitrotoluene removal in a soil slurry and soil box systems by an oil-degrading mixed bacterial culture - Jason T. Popesku; Ajay Singh; Yousef El-Alawi; Owen P. Ward (World Journal of Microbiology and Biotechnology, 2006)

Light-regulated overexpression of an Arabidopsis phytochrome A gene in rice alters plant architecture and increases grain yield - Ajay K. Garg; Ruairidh J. H. Sawers; Haiyang Wang; Ju-Kon Kim; Joseph M. Walker; Thomas P. Brutnell; Mandayam V. Parthasarathy; Richard D. Vierstra; Ray J. Wu (Planta, 2006)

Sialic acid in cardiovascular diseases - P. K. Nigam; V. S. Narain; Ajay Kumar (Indian Journal of Clinical Biochemistry, 2006)

Culture-Based Strategies for Reduction of Protease Activity in Filtrates from Aspergillus niger NRRL-3 - Aftab Ahamed; Ajay Singh; Owen P. Ward (World Journal of Microbiology and Biotechnology, 2005)

Dermal, Subdermal, and Systemic Concentrations of Granisetron by Iontophoretic Delivery - Ayyappa Chaturvedula; Dipty P. Joshi; Carter Anderson; Russ Morris; Walter L. Sembrowich; Ajay K. Banga (Pharmaceutical Research, 2005)

A Kunitz trypsin inhibitor from chickpea (Cicer arietinum L.) that exerts anti-metabolic effect on podborer (Helicoverpa armigera) larvae - Ajay Srinivasan; Ashok P. Giri; Abhay M. Harsulkar; John A. Gatehouse; Vidya S. Gupta (Plant Molecular Biology, 2005)

Biodegradation and bioremediation (series: soil biology, vol. 2) - Ajay Singh; Owen P. Ward (Journal of Soils and Sediments, 2004)

Applied bioremediation and phytoremediation (series: Soil biology, vol 1) - Ajay Singh; Owen P. Ward (Journal of Soils and Sediments, 2004)

Molecular phylogeny of mangroves VIII: Analysis of mitochondrial DNA variation for species identification and relationships in Indian mangrove Rhizophoraceae - M. Lakshmi; M. Parani; P. Senthilkumar; Ajay Parida (Wetlands Ecology and Management, 2002)

Evaluation of a mixed bacterial culture for de-emulsification of water-in-petroleum oil emulsions - Nalina Nadarajah; Ajay Singh; Owen P. Ward (World Journal of Microbiology and Biotechnology, 2002)

Biodegradation of dimethyl phthalate with high removal rates in a packed-bed reactor - Christopher Juneson; Owen P. Ward; Ajay Singh (World Journal of Microbiology and Biotechnology, 2002)

Serum ionised calcium in birth asphyxia - B. K. Jain; Daljit Singh; Harmesh Singh; A. P. S. Narang; Praveen C. Sobti; Ajay Gupta (Indian Journal of Clinical Biochemistry, 2000)

The Evolution of Enamel Microstructure: How Important Is Amelogenin? - Ajay Kishore Mathur; P. David Polly (Journal of Mammalian Evolution, 2000)

Database management and analysis for CAPE project using remote sensing and GIS - Ajay Mathur; P K Litoria; P K Sharma; M H Kalubarme (Journal of the Indian Society of Remote Sensing, 1998)

Site suitability evaluation for locating sewage treatment plants using remote sensing and gis — a case study of phillaur and phagwara townships in punjab - P K Litoria; Ajay Mathur; P K Sharma; Charan kamal Singh (Journal of the Indian Society of Remote Sensing, 1997)

Alteration of hemodynamics in aneurysm models by stenting: Influence of stent porosity - Baruch B. Lieber; Alfred P. Stancampiano; Ajay K. Wakhloo (Annals of Biomedical Engineering, 1997)